Question
Combine like terms to create an equivalent expression.
-3.6-1.9t+1.2+5.1t
Answer:
3.2t - 2.4
Step-by-step explanation:
Given;
-3.6 - 1.9t + 1.2 + 5.1t
Combining like terms means bringing terms that have "t" together and separately, those that don't have "t" together. i.e
=> − 1.9t + 5.1t - 3.6 + 1.2
=> 3.2t - 2.4
Therefore, the equivalent expression is;
3.2t - 2.4
Answer:
the last one
:D
Step-by-step explanation:
6z-7z/5=3
(30z-7z)/5=3
30z-7z=15
23z=15
z=15/23
Answer:
E. 99.7%
Step-by-step explanation:
Calculate each z-score.
z = (x − μ) / σ
z = (173 − 128) / 15
z = 3
z = (x − μ) / σ
z = (83 − 128) / 15
z = -3
You can use a z-score table, or use the empirical rule.
P(-3 < z < 3) = 99.7%.